Learning Strategies For Islamic Religious Education In The Internalization Of Religious Moderation In Indonesia - Devi Sela Eka Selvia; Dwi Kurniawan; Mediyan Pratama; Indah Resti Ayuni Suri; Erni Yusnita (Attanwir : Jurnal Keislaman dan Pendidikan, 2024)
The purpose of this research discusses Islamic education learning strategies in internalizing religious moderation in Indonesia. The study was conducted through interviews with several Islamic education teachers and students in several schools in Indonesia. The results show that Islamic education learning strategies can help students to understand the concept of religious moderation and internalize it in everyday life.One of the strategies used by teachers is to choose appropriate and relevant learning resources, such as books of hadith, Quranic verses, and other Islamic texts that support religious moderation. In addition, teachers also use modern learning media, such as videos or pictures, to explain abstract concepts in a way that is more easily understood by students.In addition, teachers also encourage critical discussions in class to help students understand the concept of religious moderation better. In such discussions, students can talk about their personal experiences in religion and how they can practice moderation in their daily lives. This research shows that Islamic education learning can be an effective way to internalize religious moderation in Indonesia. By using appropriate learning strategies, students can learn to practice moderation in daily life and maintain inter-religious harmony in Indonesia. This study has important implications for the development of Islamic education curriculum in Indonesia and can help in promoting religious moderation across the country.